2017
DOI: 10.5114/wo.2017.68628
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of squamous cell carcinoma in different sites of oral cavity at our Rural Health Care Centre in Loni, Maharashtra – a retrospective 10-year study

Abstract: Aim of the studyOral cancer ranks in the top three of all cancers in India and is quickly becoming a global health priority. More than 90% of oral and oropharyngeal cancers are squamous cell carcinoma. The purpose of this study was to document its incidence depending upon the involvement of different sites of oral cavity, and its variation with age and gender.Material and methodsHistopathologically proven oral squamous cell carcinoma cases were collected from the department of oral and maxillofacial surgery RD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 44 publications
5
84
0
4
Order By: Relevance
“…Concerning the age group, the majority of patients in the cohort were up to 65 years of age, which is similar to the demographic of patients in previous studies, showing that the typical oral cancer patients are predominantly men around the fifth and sixth decades of life (Mendez et al, 2012;Santos et al, 2010;Tandon et al, 2017). Furthermore, there is also an association seen in this study that directly relates tobacco history and alcohol intake (Durazzo et al, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Concerning the age group, the majority of patients in the cohort were up to 65 years of age, which is similar to the demographic of patients in previous studies, showing that the typical oral cancer patients are predominantly men around the fifth and sixth decades of life (Mendez et al, 2012;Santos et al, 2010;Tandon et al, 2017). Furthermore, there is also an association seen in this study that directly relates tobacco history and alcohol intake (Durazzo et al, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, Effiom et al (21) found that most of the examined OSCC cases were presented in the mandibular and maxillary alveolar ridge followed by the tongue. Moreover, Tandon et al (22) have stated that the buccal mucosa is the most prevalent location for OSCC. This was attributed to the well-known habits of areca nut-and tobacco-chewing.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 90% of all oral carcinomas are oral squamous cell carcinomas (OSCC) [128]. It has been shown previously that the invasive activity of OSCC cells is enhanced by CLDN-1 through activation of MMP-1 and 2, resulting in increased cleavage of Laminin-5 γ2 chains.…”
Section: Claudin-1 and Oral Squamous Cell Carcinomamentioning
confidence: 99%